Solidification analysis of metal matrix composites aluminium 11.8% silicon alloy reinforced with titanium carbide particulates - Fatchurrohman, Nanang (2009)
Composite is a material system composed of a mixture or combination of two or more constituents that differ in form and chemical composition and which are essentially insoluble in each other. Metal matrix composites (MMC) are engineered materials composed of an elemental or alloy as a matrix in which an insoluble second phase reinforcer is embedded and distributed to achieve property improvement. Application of MMC comprises a broad range in aircraft, automotive, defence technology and astronautics components. The performance during its work life of MMC is determined by the mechanical properties. The mechanical properties of MMC are linked to microconstituents formed and its characteristics. For MMC processed by casting method, the solidification behaviour will determine the type of microconstituents formed and its properties. In this study, casting via vortex mixing method is employed to produce MMC aluminium-ll.8% silicon alloy (LM6) reinforced with different volume percentages (0,5,10,15,20,25%) of titanium particulates (TiCp) cast using sand and copper moulds. Temperature measurements during cooling and solidification are used as the main source to analyse solidification properties (fraction solid and latent heat generation) using Fourier thermal analysis method. A metallographic study is performed to observe the particulates distribution and microconstituents present. A hardness test is carried out, the results show that 25% volume addition ofTiCp cast using copper mould has the best result. This result correspond to the improved microstructure as particulates are well distributed in the matrix which can be seen on the photomicrographs. From the visual observation of photomicrographs, the increment addition of particulates will promote more nucleation sites and grain size is reduced due to faster solidification of casting using copper mould (high heat extraction capacity). For production using sand mould the maximum mean value of hardness 54.38 Rockwell number is reached by addition of 25% volume content TiCp , solidification time (fraction solid equals to 1) at 195 seconds and volumetric latent heat generated 245.63 103kJ/m3. The best result is obtained by fabrication of LM6- TiCp MMC using copper mould (permanent die), the maximum mean value of hardness 76.82 Rockwell number is reached by addition of 25% TiCp volume content, solidification time (fraction equals to 1) at 5 seconds (fastest) and volumetric latent heat generated 100.77 kJ/m3. From the results, it is concluded that casting of LM6- TiCp MMC is successfully achieved using vortex mixing technique and that addition of particulates influence solidification characteristics which in turn affect the properties of the MMC.